Revenues from agricultural tax in the context of the principle of financial independence of municipalities - Życzkowska, Elżbieta; Dziuba, Jarosław (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The presented study addresses the important and current problem of agricultural tax and the resulting revenues in the context of financial independence of local government units. The scope of financial independence held by a municipality is significantly influenced by the right to exercise limited fiscal power. It means that the state provides municipalities with a number of powers to shape the local tax system, to set tax rates, to introduce individual tax exemptions, allowances and amortizations. Aim: The main purpose of the article is to present the importance of agricultural tax as the source of generating own revenues by municipalities in Poland, in the years 2015–2019, in the context of the principle of financial independence of municipalities. The supplementary purpose is to analyse and assess exercising the rights in terms of shaping revenues from agricultural tax in municipalities. Results: The analysis covers the level and share of revenues from agricultural tax in total revenues and municipal own revenues as well as the amount of revenues lost on its account. The conducted research has shown that agricultural tax plays the greatest role as the source of own revenues in managing the budgets of rural municipalities. However, it can be noticed that the fiscal function of the tax under study is increasingly smaller in each municipal category. It should be indicated that the structure of agricultural tax, which is basically unrelated to profitability and the volume of production in agriculture, in turn, translates into a low level of own revenues potential in municipalities. The system of taxing agriculture with agricultural tax, from the perspective of financial independence of municipalities, remains ineffective and the degree of independence presented by municipalities in this respect is far from a satisfactory level. The conducted analysis addressing correlations resulting from various types of reductions in agricultural tax against revenues from this tax showed that the scale of reductions, as the effect of using various tools by municipalities, was minimal and did not exceed 1% (which makes approx. 0.5%). The exception is the possibility of reducing the upper tax rates by a municipality.